Deconstruction of Religious Education in the Postmodern Era - Neda Mohajel; Muhammad Asghari (Journal of Philosophical Investigations, 2023)
In this article, we are trying to show that in the postmodern era, by questioning the ontological foundations of theology and rejecting absolutism and embracing pluralism and relativism, religious education has been placed in an anti-realistic postmodern framework. This type of education and training tries to replace the horizontal and context-oriented or local view by rejecting the vertical-oriented view in traditional and modern education and training, in which transcendental and absolute values are accepted, and this is the method of deconstructing this type of education and training that has been proposed under the influence of postmodern philosophers such as Derrida. This type of education is expanding and growing in the 21st century. But this approach itself also faces problems that cannot be completely general. Negation of the essence and nature of religion, failure to recognize the essence of religion, considering religious experience to be historical and local, etc. in this approach indicates its insufficiency in its complete spread throughout the world. Therefore, it seems that critical education is a suitable alternative to post-modern religious education in order to familiarize students with the nature and essence of religion and to accept pluralism and contextualism in their own education.